Development of intensiometric indicators for visualizing N-cadherin interaction across cells - Takashi Kanadome; Kanehiro Hayashi; Yusuke Seto; Mototsugu Eiraku; Kazunori Nakajima; Takeharu Nagai; Tomoki Matsuda (Communications Biology, 2022)
Intensiometric N-cadherin (NCad) interaction indicators, named INCIDERs, visualize reversible NCad-mediated cell-cell interactions.